The Relationship Between Transformational Leadership and Organizational Loyalty -Case Study of the Algeria Water Entreprise, Bechar- - Berbaoui, Kamel; Kanachi, Amna (Finance and Business Economies Review, 2019)
The study aimed to determine the relationship between transformational Leadership and organizational loyalty. In order to reach this objective, a questionnaire was developed and distributed to the study sample (Algerian Water Workers Unit of Bechar) for the purpose of data collection. The statistical analysis of this study has been relying on the spss program .The findings of the study show that there are statistically significant relationships between transformational leadership and organizational loyalty, idealized influence and organizational loyalty, inspirational motivation and organizational loyalty, , intellectual simulation and organizational loyalty, and between individual attention and organizational loyalty